2019
DOI: 10.1111/1750-3841.14813
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Microorganisms Associated with the Quality Improvement of Dry‐Aged Beef Through Microbiome Analysis and DNA Sequencing, and Evaluation of Their Effects on Beef Quality

Abstract: The objective of this study was to isolate and identify the microorganisms, especially yeasts and molds, related to the improvement of beef quality during dry‐aging of beef through microbiome analysis, and to examine the possibility of using them as starter culture strains to improve the efficiency of dry‐aging beef production. Beef sirloins were dry‐aged for 28 days using different wind speeds (0, 2.5, and 5 m/s) at 1 to 3 °C and 75% relative humidity, and microbial compositions were confirmed by microbiome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
2
28
0
2
Order By: Relevance
“…However, L-tryptophan and ornithine increased between 0 and 2 D of storage and between 0 and 4 D of storage, respectively, after which they both decreased. The actions of endogenous proteases and microorganisms are associated with free amino acid generation ( Yang et al., 2016 , Oh et al., 2019 , Wickramasinghe et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, L-tryptophan and ornithine increased between 0 and 2 D of storage and between 0 and 4 D of storage, respectively, after which they both decreased. The actions of endogenous proteases and microorganisms are associated with free amino acid generation ( Yang et al., 2016 , Oh et al., 2019 , Wickramasinghe et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Debaryomyces hansenii has been identified as one of the major microbes in DA beef (Oh et al, 2019), and its beneficial properties, including the degradation of biogenic amines and production of volatile sulfur compounds in meat products, have been reported (Baumlisberger et al, 2015; Perea‐Sanz et al, 2019). Therefore, this organism is a starter candidate for several meat products (Murgia et al, 2019; Oh et al, 2019; Ramos et al, 2017), but not yet for DA pork. Collectively, the present results and previous findings suggest that this organism is a promising starter for DA pork.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this organism is a starter candidate for several meat products (Murgia et al, 2019;Oh et al, 2019;Ramos et al, 2017), but not yet for DA pork. Collectively, the present results and previous findings suggest that this organism is a promising starter for DA pork.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [8] observed significant increases in levels of flavor compounds of dry-aged beef between day 21 and 28, and explained that further proteolysis and lipolysis associated with microorganisms (especially mold and/or yeast) could develop aroma compounds of dry-aged beef. Oh et al [42] observed that dry-aged beef inoculated with Pilaira anomala had higher oleic, palmitic, and stearic acid content at day 21, while inoculation with D. hansenii resulted in higher amounts of free amino acids at day 28. Finally, the contribution of 2-methylpropanal, 2-methylbutanal, 2-methyl-2-propanethiol, ethyl propanoate, and possibly 2-methylpropanoic acid to dry-aged flavor should be noted when their low odor threshold values (Table 2) and concentration differences between dry-and wetaged beef are taken account (Tables 3, 5 and 7).…”
Section: Volatile Patterns Of Aged Beefmentioning
confidence: 99%